Poetry and Sustainability in Education - Kleppe, Sandra Lee.; Sorby, Angela (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This edited collection offers educators at all levels a range of practical and theoretical approaches to teaching poetry in the context of environmental sustainability. The contributors are keenly aware of the urgency facing the planet's ecosystems-ecosystems which include all of us-and this volume makes the case that teaching poetry is not a luxury. Each of the book's three sections works from a specific angle and register. Part I focuses on pragmatic approaches to classroom activities and curricular choices; Part II considers policies and politics, including the role of the UN's Education for Sustainable Development (ESD) program; and Part III takes a widescreen view, exploring the philosophical issues that arise when poems are integrated into sustainability curricula. This book exemplifies how poetry empowers readers to think imaginatively about how to sustain-and why to sustain-our world, its resources, and its beauty. Sandra Lee Kleppe is Professor of English-language literature at Inland Norway University. She is author of The Poetry of Raymond Carver: Against the Current (2013), editor/co-author of Ekphrasis in American Poetry: The Colonial Period to the 21st Century (2015), and co-editor/co-author of Poetry and Pedagogy across the Lifespan: Disciplines, Classrooms, Contexts (with Angela Sorby, 2018). Angela Sorby is Professor of English at Marquette University. Her prior books include Distance Learning (1998); Schoolroom Poets (2005); Bird Skin Coat (2009); The Sleeve Waves (2014); Over the River and Through the Wood (with Karen Kilcup, 2013); and Poetry and Pedagogy Across the Lifespan (with Sandra Kleppe, 2018). .
PART I: LEARNING WITH THE BIOSPHERE: BIRDS, BEES, FLOWERS AND TREES -- Chapter 1. Birdsong, Poetry and Sustainability in Education -- Chapter 2. "Hanging on for the Bees": Teaching with Sylvia Plath's Bee Poems -- Chapter 3. "These Things Never Happened but Are Always": Why Tree Poems Matter -- Chapter 4. Listening to Animals for a Change. On Teaching Animal Poetry from a Critical Rhetorical Perspective -- Chapter 5. Indigenous Poetry and Sustainability: Troubling Anthropocene Logic through Kinship, Wholeness and Care -- PART II: POETIC LITERACY AND EDUCATION FOR SUSTAINABLE DEVELOPMENT -- Chapter 6. Poetic Learning for a Sustainable Future: Transforming Our Collective -- Chapter 7. "Whose Action Is No Stronger than a Flower?": Poetry, Education and Environmental Crisis -- Chapter 8. First World War Poetry and Historical Literacy -- Chapter 9. Ecopoetry, Pedagogical Encounters and Holding Absence Present: Ideas for Classrooms PART III: POETS, PHILOSOPHERS, AND THE PLANET -- Chapter 10. Towards a Pedagogy of The Transversal: Using Félix Guattari's Ecosophical Aesthetics for Teaching Poetry -- Chapter 11. "Right has just left": Learning from Concurrency and the Experiential Aspect of the Ongoing in Cia Rinne's Poetic Work -- Chapter 12. The Message of Poetry or Poetry as Messenger: The Poetics of Sustainability in the Pedagogical Context -- Chapter 13. Towards a Sustainable Imagination: Reflections on Olav H. Hauge and the Teaching of Poetry.
Keywords: Environmental education; Inclusive education; Poetry; Environmental and Sustainability Education; Inclusive Education; Poetry and Poetics